Analisis Perbandingan Portofolio Optimal Model Markowitz dan Model MVEP (Studi Kasus Saham LQ-45 di Bursa Efek Indonesia di Masa Pandemi Covid-19) - Silvia, Ade; Rosha, Media (Journal of Mathematics UNP, 2024)
Investing involves allocating funds with the expectation of future profits. The higher the expected return, the higher the risk one must assume. Optimal portfolios are designed to minimize risk while maximizing returns. The Markowitz model and the Mean Variance Efficient Portfolio (MVEP) are two methods that can be used to construct such portfolios. This study aims to compare the optimal portfolios of LQ-45 stocks during the Covid-19 pandemic using both the Markowitz model and the MVEP model, and to evaluate the performance of these portfolios by calculating the Sharpe ratio index. The analysis reveals that the optimal portfolio formed using the Markowitz model outperforms the one formed using the MVEP model